Kant on the History of Humankind: the Invisible Hand of Nature Behind the Progress of the Realization of Freedom - Havugimana, Théogène (Faculdade de Filosofia e Ciências, 2018)
In his essay, “Idee zu einer allgemeinen Geschichte in weltbürgerlicher Absicht” (1784), Kant claims that the history of mankind should reflectively be understood as a process thanks to which the human race ‘as a whole’ gradually approximates its terminus ad quem, i.e., the establishment of “a moral whole” (ein moralisch Ganze). (IaG AA 8:21). In objection to the empirical standpoint adopted by historiographers’ account of natural history, Kant shows that his intention is far from elaborating a “history…written merely empirically” (IaG AA 8:30), i.e., “history which concerns itself with the narration of… appearances” (IaG AA 8:17).